TAJIKISTAN’S GEOPOLITICAL LANDMARKS - BAKHOVADINOV, Aloviddin; DODIKHUDOEV, Khurshed (CENTRAL ASIA AND THE CAUCASUS, 2005)
Foreign policy of any state is designed to protect its national interests with the help of instruments ranging from military-political and economic to cultural and ideological. At the same time, there are some states unable or unwilling to create or apply such instruments. While pursuing their strategic interests, they prefer to coordinate their foreign policies with those of the world’s centers of power. Tajikistan belongs to this latter group. Having paid dearly for its newly acquired independence, it is actively developing its contacts with the rest of the world. In the early 1990s, the country’s leaders regarded cooperation with the CIS, the Russian Federation in the first place, as their absolute priority. Later, however, in the last few years of the 20th century Tajikistan’s foreign policy acquired many more vectors. Before going into details, let’s look at the young Tajik state. It is a small country that covers 143,100 sq km (93 percent of its territory being mountains). Tajikistan is found in the southeastern corner of Central Asia and borders on Kyrgyzstan, Uzbekistan, Afghanistan, and China. The country is rich in coal, marble, gold, silver (its de posits come second in the world after Mexico), tungsten, lead, uranium, zinc, etc. Sixty-five percent of the Central Asian water resources are also found in Tajikistan. From time immemorial, its territory was part of the Great Silk Road that stitched together the major Eurasian cultural and economic areas: China, Central Asia, India, the Middle and Near East, the Mediterranean, and Europe. This was why all world empires (the Persian Empire, the Arabian Caliphate, the Russian Empire and its heir the Soviet Union) never let the country out of sight. At different periods the territory saw all great conquerors: Alexander the Great, Genghis Khan and Tamerlane. Today, one can discern traces of Aryan, Buddhist, Islamic, and Orthodox Christian civilizations in Tajikistan, which helps our republic cooperate with the nations belonging to these civilizations.